(untitled) (Global Journal of Management and Business Research, 2019)
Every enterprise in Nigeria depends on refined petroleum product for either transportation, power, or heat source. The recurrent shortages or scarcity of petroleum products in Nigeria cripples business activities, which undermines the development of the economy. The purpose of this multiple case study was to identify the strategic role of finance, banks, and foreign exchange in mitigating petroleum shortages in the petroleum supply chain and to sustain business development in Nigeria. The study participants include ten senior leaders from two private-sector Nigerian downstream petroleum supply companies located in the Niger Delta region, who had successfully implemented strategies for petroleum supply. The resource based view theory served as the conceptual framework for the study. Data were collected through semi structured face-to-face interviews and review of operational and policy documents from the supply or marketing companies.